FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TEKANAN DARAH PASIEN HIPERTENSI - Ramarianda, Ninda Putri (Politeknik Kesehatan Kemenkes Bengkulu, 2015)
Hypertension is often referred to as the silent killer. Hypertension is a condition of elevated bloodpressure in the arteries that lead to increased risk for stroke, aneurysm, heart failure, heart attack and kidneydamage. Some of the causes of hypertension were age, sex, carbohydrate intake, saturated fat and unsaturatedfat. The purpose of this study to determine the factors that most influence the blood pressure of hypertensivepatients. This type of research analytic survey with a cross-sectional design with independent variables (age,sex, carbohydrate intake, saturated fat and unsaturated fat) and the dependent variable (blood pressure). Totalpopulation of 476 hypertensive patients. Samples taken by accidental sampling. The Total samples is 83. Theresults showed that there is a significant relationship between age, intake of carbohydrates, saturated fat andunsaturated fat with blood pressure. There is no significant difference in blood pressure between the sexes. Themost dominant factor is the systolic blood pressure is age and diastolic blood pressure is carbohydrate intake.